2003
DOI: 10.1039/b302080k
|View full text |Cite
|
Sign up to set email alerts
|

A novel migrative addition reaction of hydrazines to the diketone derivative of C60Electronic supplementary information (ESI) available: experimental procedures and characterisation data; computational procedures and Cartesian coordinates of 3a-I. See http://www.rsc.org/suppdata/cc/b3/b302080k/

Abstract: A novel addition reaction of an aromatic hydrazine to the diketone derivative of C60 occurs highly regioselectively with an unusual migration of two hydrogen atoms from the hydrazine to the fullerene and affords a fluorescent product having a methylene carbon along the orifice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 13 publications
2
29
0
Order By: Relevance
“…However, the ES-mass spectrum of 11a showed a parent ion peak at m/z = 1144, indicating that the product was an exact 1:1 adduct without any elimination. 39 carbon was observed at d = 43.80 ppm. The 13 C NMR spectrum of the 13 C-enriched 11a suggested that the methylene carbon was derived from the C 60 cage.…”
Section: Expansion Of the Orifice Of The Open-cage Diketone C 60 (1) mentioning
confidence: 94%
See 2 more Smart Citations
“…However, the ES-mass spectrum of 11a showed a parent ion peak at m/z = 1144, indicating that the product was an exact 1:1 adduct without any elimination. 39 carbon was observed at d = 43.80 ppm. The 13 C NMR spectrum of the 13 C-enriched 11a suggested that the methylene carbon was derived from the C 60 cage.…”
Section: Expansion Of the Orifice Of The Open-cage Diketone C 60 (1) mentioning
confidence: 94%
“…One cage scission is essential to convert a fullerene carbon to a methylene carbon. By further structural analyses of selective INADEQUATE, HMBC, and 15 N NMR, 39 we concluded that one carbon-carbon bond, C(4)-C(5) in Scheme 9, was cleaved to give 11a having a methylene carbon along the rim. Compound 11a has an acenaphthenequinone monohydrazone as its partial structure, and the carbonyl absorption in IR and the chemical shift of the NH proton in 1 H NMR showed good agreement with those of the corresponding compound.…”
Section: Expansion Of the Orifice Of The Open-cage Diketone C 60 (1) mentioning
confidence: 97%
See 1 more Smart Citation
“…[55] Indisputable structural assignment would come from X-ray diffraction analysis. Analogous reactions of hydrazine or hydrazone or phenylenediamine with the diketone 30 provided the corresponding 46 [56] and 47 [57] with even larger holes. These hole-enlargement reactions are unprecedented in classical organic reactions; their mechanism remains unknown.…”
Section: Hole-enlargement Reactionsmentioning
confidence: 99%
“…29 Thus, the opening of diketone 13 was greatly enlarged as reported by Iwamatsu et al Although the detailed reaction mechanism is not clear yet, a reaction of 13 with a phenyl hydrazine proceeded at room temperature to give open-cage fullerene 14 having an sp 3 methylene carbon within the rim of a 16-membered-ring opening. 30 The size of the ellipsoidal opening was estimated to be 6.5 Å for a longer axis and 3.8 Å for a shorter axis (B3LYP/3-21G level). When a solution of 14 in 1,1,2,2-tetrachloroethane-d 2 (TCE-d 2 ) was heated under 133 atm of H 2 gas at 100 1C for 4 h, encapsulation of a H 2 molecule took place to give H 2 @14 at an occupation level of 62%.…”
Section: Bowl-shaped Fullerenesmentioning
confidence: 99%